Multilevel analysis of infant sunlight exposure practices among mothers in Mettu district Illubabor zone Oromia Ethiopia - Woldemariam Erkalo Gobena (Scientific Reports)
Abstract Infants can get enough vitamin D from regular sunlight exposure. It is required in infants to prevent rickets, minimize the danger of life-threatening hypocalcemic consequences, boost the immune system, and aid in the prevention of cancer, diabetes, and other chronic disorders. The aim of the study was to identify the individual and community-level factors of the practice of sunlight exposure in infants. A community-based cross-sectional study design was undertaken to collect data from March 2024 to April 2024. The multilevel mixed-effects model was used to identify significant factors associated with the practice of sunlight exposure in infants. 372 (58.13%) mothers, out of 640 participants, practiced adequate exposure of their infants to sunlight. The result of multilevel mixed-effects analysis revealed that rural mothers had lower odds of adequately exposing their infants to sunlight when compared with urban mothers [AOR = 0.34, 95% CI = 0.16–0.52]. The finding of this study revealed that 58.13% of mothers have good practices of sunlight exposure. The current study also revealed that there was variation among rural and urban women on the good practice of sunning their infants. Mothers need to be educated about the benefits of infants’ sunlight exposure. Further studies should be conducted to determine the best way to sun infants in order to maintain adequate vitamin D that helps the body to absorb calcium to strengthen bones, thereby preventing rickets and other childhood disorders.